Sore throat as a side effect of abobotulinum toxin A injection for upper limb spasticity after stroke: A case report - KARADAĞ SAYGI, NAİME EVRİM (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2020)
Despite sore throat exists in the product characteristics of abobotulinum toxin A as one of the side effects, no available reports of sore throat after abobotulinum toxin A injection for adult upper limb spasticity could be found in the literature to guide physicians for the management. Herein, we report a case of poststroke spasticity who develop sore throat immediately after abobotulinum toxin A (Dysport) injection of forearm muscles which completely resolved after observation for eight hours. This case report highlights a rare side effect of abobotulinum toxin A and provides information regarding the follow-up process of side effects which would guide physicians for the management.
Keywords: Adverse drug event; botulinurn toxins type A; sore throat; spasticity